UJI KANDUNGAN BAKTERI E-COLI PADA AIR MINUM DALAM KEMASAN BEBERAPA PRODUK LOKAL PANTAI BARAT SELATAN ACEH - Zaulfikar Abbas; Wintah Wintah (Jurnal Optimalisasi, 2015)
As the ever-increasing water demand, especially consumption, has prompted the emergence of a variety of drinking water business, both of Bottled Drinking Water (bottled water) as well as drinking water refill. Each of drinking water produced, must meet the quality requirements set by the Minister of Health of the Republic of Indonesia. Among these are the quality requirements of drinking water must be free of bacteria or germs. E-coli bacteria in the body can cause intestinal fever or dysentery. If late untreated can result in death due to loss of body fluids.The main purpose of this study was to determine that the Bottled Water production South West coast of Aceh free from the content of the e-coli bacteria according to the Minister of Health of the Republic of Indonesia Number 492 / Menkes / PER / IV / 2010. It can be concluded Bottled Drinking Water (bottled water) is safe or not for public consumption.To carry out this study, researchers using descriptive method is based on laboratory test results. The technique of sampling was done by purposive sampling, where each brand is taken three (3) samples of drinking water in the glass packaging 220-230 ml of markets / locations. Observation, researchers found seven brands of Bottled Drinking Water (bottled water). Tests conducted repetition 2 times. So the total number is 42 samples tested.The results showed that of the 42 samples test negative results the content of the e-coli bacteria. From the results obtained it can be concluded that the seven brands of Bottled Drinking Water (bottled water) production area of the West Coast of South Aceh is safe for public consumption because it is free of the content of the e-coli bacteria.Kewords : bakteri e-coli, bottled water, water production, healthy